Linaria subbaetica (Plantaginaceae), a new species from the south of the Iberian Peninsula - Blanca, Gabriel; Cueto, Miguel; Fuentes, Julián (Phytotaxa, 2022)
Linaria subbaetica, a new species from the south of the Iberian Peninsula, is here described, illustrated, and compared with its morphologically closest relatives from L. sect. Supinae: L. badalii, L. caesia, and L. supina. The species is characterised by being annual, and having usually revolute leaves, a short and corymbiform inflorescence at anthesis with a pilose-glandulose axis, a white to pale-yellow corolla (yellow to orangish palate), bearing a spur equalling to slightly longer that the rest of the corolla, and black seeds with a tuberculate and papillose disc surface and a thickened wing. L. subbaetica is an endemic species, growing on calcareous mountains, in the Sierras Subbéticas Natural Park, Córdoba province (Andalusia, Spain).